New Approach to Enrich Pasta with Polyphenols from Grape Marc. (25th November 2015) - Marinelli, V.; Padalino, L.; Nardiello, D.; Del Nobile, M. A.; Conte, A.
Abstract : Food industry produces significant amount of waste that represents a problem for the sector. However, by-products are also promising sources of compounds which may be reused for their nutritional properties. The aim of this work is to exploit wine-making by-products, obtaining an extract by ultrasound-assisted extraction only using water as solvent. The characteristics of spaghetti enriched with grape marc were assessed and compared to control samples. In particular, total phenolic and flavonoids contents, the antioxidant activity, the cooking quality, and the sensory acceptability were evaluated at various steps of pasta production. The enriched spaghetti showed higher total phenolic and flavonoids contents and higher antioxidant activity than the control pasta. In addition, low cooking losses were found. In terms of sensory properties fortified pasta is acceptable as the traditional product, thus demonstrating that it is possible to exploit food waste to better satisfy consumer demand for healthy food products in a more sustainable perspective.